Fully Automatic In-Syringe Magnetic Stirring-Assisted Dispersive Liquid-Liquid Microextraction Hyphenated to High-Temperature Torch Integrated Sample Introduction System-Inductively Coupled Plasma Spectrometer with Direct Injection of the Organic Phase - Sánchez, Raquel; Horstkotte, Burkhard; Fikarová, Kateřina; Sklenářová, Hana; Maestre, Salvador; Miró, Manuel; Todolí, Jose-Luis (Analytical chemistry, 2017)
A proof of concept study involving the online coupling of automatic dispersive liquid-liquid microextraction (DLLME) to inductively coupled plasma optical emission spectrometry (ICP OES) with direct introduction and analysis of the organic extract is herein reported for the first time. The flow-based analyzer features a lab-in-syringe (LIS) setup with an integrated stirring system, a Meinhard nebulizer in combination with a heated single-pass spray chamber, and a rotary injection valve, used as an online interface between the microextraction system and the detection instrument. Air-segmented flow was used for delivery of a fraction of the nonwater miscible extraction phase, 12 μL of xylene, to the nebulizer. All sample preparative steps including magnetic stirring assisted DLLME were carried out inside the syringe void volume as a size-adaptable yet sealed mixing and extraction chamber. Determination of trace level concentrations of cadmium, copper, lead, and silver as model analytes has been demonstrated by microextraction as diethyldithiophosphate (DDTP) complexes. The automatic LIS-DLLME method features quantitative metal extraction, even in troublesome sample matrixes, such as seawater, salt, and fruit juices, with relative recoveries within the range of 94-103%, 93-100%, and 92-99%, respectively. Furthermore, no statistically significant differences at the 0.05 significance level were found between concentration values experimentally obtained and the certified values of two serum standard reference materials.